(3cJGH ajg SjGSI GdCeQGA hdGI GdLfhO hGdeJVef dKdGKI YghOs - (3EHQGgje Hf YHO GdhGMO Hf CHj GdfhQs
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd ef TGA ef GdNdjbI HJaVjdI CeG HYO aEf Gddg bO TQafG hCSYOgG HgPg GdOhdI GdYdjI GdeQaYI GdQVjI GdehdhjI GdeJhcdjI OhdI SjOfG hehdGfG GdNdjaI GdEeGe GdeJhcd Ydi Gddg s
(3BNQgG (B:s
(3Ch YjdI RGOJ RGjOgG Ydi ebOGQ EcJSGHg hGdMeO ddg QH GdYGdejf s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(719) s
Keywords: (3GdSjGSI hGdGLJeGYs